Automatic monitoring of water pollution with emphasis on biological monitors - Peralta, Genandrialene L.
Recent developments in the field of automated monitoring systems include state of the art instrumentation which makes full use of existing computer technology and automation processes in environmental monitoring. This paper will describe the various technologies in automatic monitoring of water pollution, ranging from biological to physico-chemical methods with stress on biological monitors as they are fast gaining attention from researchers worldwide, offering great promise in the future especially in developing countries.